A qualitative analysis of the social regulation of violence in a Cornish school 1999-2003 - Myers, Carrie Anne (2004)
This thesis demonstrates the day-to-day experiences of victimisation and opinions about crime as they were encountered by a group of pupils in a rural school at one particular point in time. A number of key themes are addressed, the first being the notion of the adolescent as a victim of crime. This thesis considers what 'crime' means to the pupils at this school and documents their views of crime in the wider community. The next area addressed is the victimisation of adolescents by fellow adolescents; here the focus is on incidents of bullying that occurred on and off the school premises. Thirdly, boys as victims is an under-researched subject matter. this is regarded and the question of masculine identities is included. Furthermore, the roles the female students play are investigated, paying particular attention to their involvement in acts of violence and bullying. The fourth area explore the limits of moral conduct and how this particular age group makes decisions about the unwritten moral codes and boundaries affecting the display of violence. This in tum invites the question of how teenagers made sense of larger moral problems and problems of living inside a school interpreted as a form of institution with a distinctive 'underlife'. These themes are addressed within an analysis of the larger social organisation of childhood and adolescence. Criminologists have long recognised the importance of peer group influence in the development of offending behaviour, but the research took into account the rural context of that setting, the final analytical lens through which it is focussed. This thesis demonstrates that the intricate patterns of violence and bullying are a process whereby status and power reinforce an established hierarchy of pupil's informal relations. The importance of the peer group emerged as the key to understanding interactions between the pupils at the school researched. The power of the peer group would have to be taken into consideration in any strategies devised to curtail bullying